Determination of the Reference Crop Evapotranspiration (ETo) for Designinig Irrigation Equipment in Uruguay - García Petillo, Mario; Puppo, Lucía (Agrociencia Uruguay, 2015)
The maximum reference crop evapotranspiration (ETo) is the starting point for irrigation systems design. With this value it is posible to calculate the design flow which leads to the most economic equipment that ensures the potential crop growth. The concept of maximum ETo is not a single value as would be the absolute maximum, but varies according to the period considered (daily, weekly, decadal, monthly) and the probability of non-exceedence. In this paper daily ETo time series, between 28 and 35 years, recorded in January at the five experimental stations of National Institute of Agricultural Research (INIA) were analyzed. Daily ETo values with 80 % probability of non-exeedence were significantly higher than those calculated based on decadal or monthly data. The latter two were quite similar, ranging from 0.1 to 0.3 mm d-1 in the different experimental stations. In the south (Canelones and Colonia), daily ETo values were as high as in the north (Salto), but in Salto the ETo values remained higher for longer periods. The aim of this study was to recommend an ETo value which can be used for irrigation equipment design anywhere across the country. As a result, a map of Uruguay with ETo isolines based on decadal data with 80 % probabilityof non-exceedence is presented.